2015
DOI: 10.3724/sp.j.1123.2015.08031
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 2-methylisoborneol and geosmin in drinking water using headspace solid phase micro-extraction coupled with gas chromatography-mass spectrometry

Abstract: The odorous compounds of 2-methylisoborneol (2-MIB) and geosmin (GSM) heavily produced and released in water source are one of the most important factors leading to off-flavor emergencies and resident water consumption panic in drinking water. A headspace solid phase micro-extraction ( HS-SPME) combined with gas chromatography-mass spectrometry (GC-MS) method was established for the simultaneous determination of these two trace earthy and musty compounds in reservoir water, reservoir soil and tap water. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The DMTS fitted curve image shows that the peak area of DMTS was more in equilibrium and stable until the ion concentration reached 20%, after which it began to decline. Numerous researchers have chosen a 20% ion concentration as the extraction condition in single-variable optimization experiments [18,20], and the results in this study were similar; that is, the maximum extraction peak area of DMSs was found at a 20% ion concentration. Based on the fitting results of the three DMSs, 16%, 18%, and 20% were selected as the three ion concentrations in the orthogonal optimization experiments to further refine the optimal ion concentration.…”
Section: Optimization Of Ion Concentrationsupporting
confidence: 59%
See 4 more Smart Citations
“…The DMTS fitted curve image shows that the peak area of DMTS was more in equilibrium and stable until the ion concentration reached 20%, after which it began to decline. Numerous researchers have chosen a 20% ion concentration as the extraction condition in single-variable optimization experiments [18,20], and the results in this study were similar; that is, the maximum extraction peak area of DMSs was found at a 20% ion concentration. Based on the fitting results of the three DMSs, 16%, 18%, and 20% were selected as the three ion concentrations in the orthogonal optimization experiments to further refine the optimal ion concentration.…”
Section: Optimization Of Ion Concentrationsupporting
confidence: 59%
“…The fitted DMDS curve showed that the peak area of DMDS exhibited a roughly parabolic trend with the increase in extraction temperature, and reached the maximum value when the extraction temperature was 55 • C. The curve fitting of DMTS showed that the DMTS peak area increased logarithmically with an increase in the extraction temperature, the growth rate increased, and the effect of the extraction temperature on the peak area of DMTS was most significant. The extraction temperature should not be too high, or it will cause water vapor to attach to the extraction fiber, affecting the extraction and adsorption of the target analytes [20]. In this study, the optimal extraction temperatures for DMS and DMDS were not excessively high.…”
Section: Optimization Of Extraction Temperaturementioning
confidence: 84%
See 3 more Smart Citations